2017
DOI: 10.1109/tip.2017.2706502
|View full text |Cite
|
Sign up to set email alerts
|

Features Classification Forest: A Novel Development that is Adaptable to Robust Blind Watermarking Techniques

Abstract: A novel watermarking scheme is proposed that could substantially improve current watermarking techniques. This scheme exploits the features of micro images of watermarks to build association rules and embeds the rules into a host image instead of the bit stream of the watermark, which is commonly used in digital watermarking. Next, similar micro images with the same rules are collected or even created from the host image to simulate an extracted watermark. This method, called the features classification forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…To unclear the image outside recognition, it is possible to perform mapping a number of times. The mapping can be done successively many times to completely unclear the image beyond recognition (13) . Alice has the information about the number of times the transform is applied and can successfully recover the original image.…”
Section: Arnold Transformmentioning
confidence: 99%
See 1 more Smart Citation
“…To unclear the image outside recognition, it is possible to perform mapping a number of times. The mapping can be done successively many times to completely unclear the image beyond recognition (13) . Alice has the information about the number of times the transform is applied and can successfully recover the original image.…”
Section: Arnold Transformmentioning
confidence: 99%
“…The authors observed that the quality of watermarking has been high with performance results. The concept of logo watermarking has been suggested (12,13) . Single level decomposition is to embed a trivial symbol with level decomposition for the host image and the Arnold transform is introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the stability of SVD, that is, small numerical changes of singular values or the correlation of feature invariant elements in singular vectors after different attacks, these methods were reported to be robust to most attacks. Chang et al [19] proposed a model that exploits the features of watermarks to establish association rules and embeds the rules into a host image. Their model combined with SVD technology can resist different image processing attacks.…”
Section: Introductionmentioning
confidence: 99%
“…For the better selection of features used features optimization process. The process of features optimization used swarm-based optimization algorithms [9,10,21]. The swarm-based algorithms are multi-objective and multi constraint-based fitness function and generate a better optimal solution instead of unguided algorithms for the optimization of features used particle swarm optimization and ant colony optimization [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%